Application of Grey-Fuzzy Approach for Optimization of CNC Turning Process. (2018) - Palanisamy, D.; Senthil, P.
Abstract: This present investigation details the determination of optimum machining conditions for turning of PH stainless steel by grey fuzzy approach which is a fast and effective optimization technique having combinatorial advantages of both grey system and fuzzy logic approach. Taguchi's design of experiment method is employed for designing and an L27 orthogonal array is selected for performing the experiments. The cutting speed, feed rate and depth of cut are considered as input variables. The surface roughness and power consumption are deemed as performance characteristics. Taguchi based grey system approach and grey-fuzzy grade are used to evaluate the relationship between input variables and performance measures. To convert the multi-quality characteristics into a single performance index, the fuzzy inference system is used. It is proved from the investigation that the proposed method of optimization technique improves the multi performance characteristics effectively.